Polycrystalline diamond obtained in the diamond-Mo system with enhanced thermal stability sintered by HPHT - Laurindo, Quézia Manuela Gonçalves (2024)
This study provides thermoanalytical data on polycrystalline diamond (PCD) sintered in the diamond-Mo system at high pressure-high temperatures (HPHT). PCD is a key material for the abrasive tool industry, given its unprecedented hardness and wear resistance, as well as its excellent thermal conductivity. These characteristics make it highly effective in drilling into rock formations and machining non-ferrous materials, such as titanium alloys. A critical issue in the performance and lifetime of polycrystalline diamond, however, is its low thermal stability, which limits its potential applications. Accordingly, PCD with enhanced thermostability was obtained in the diamond-Mo system, with resistance graphitization and oxidation around 200 °C higher than conventional PCD. The superior thermal performance seen for PCD-Mo may be due to the formation of in situ carbides (MoC and Mo2C), which inhibit the evolution of graphitization and oxidative processes.